Comer y ser : raíces gastronómicas de México - Armella, Nathalie (CACCIANI, S.A. de C.V. : Fundacion Cultural Armella Spitalier, 2012)
Reflections on pre-Hispanic roots of Mexican cuisine, illustrated with numerous photographs of codices, earthenware vessels, local produce, cooking instruments, and ingredients. Includes essays on rites and offering, crop cultivation, commerce and trade, variety of foods, types of meals, and relationship between food and death.